"An Active, Productive Life": Narratives of, and Through, Participation in Public and Patient Involvement in Health Research. (December 2020) - Reynolds, Joanna; Beresford, Ruth
Public and patient involvement (PPI)—engaging the public in designing and delivering research—is increasingly expected in health research, reflecting recognition of the value of "lay" knowledge of illness and/or caring for informing research. Despite increased understanding of PPI experiences within the research process, little attention has been paid to the meaning of PPI in other areas of contributors' lives, and its value as a broader social practice. We conducted repeated narrative interviews with five experienced PPI contributors from the United Kingdom to explore how meaning is constructed through narratives of PPI in relation to their broader "life-worlds." Narratives were extremely varied, constructing identities and meanings around PPI in relation to family and social life, career and employment, financial status, and wider social agendas, as well as health. This emphasizes the importance of recognizing PPI as a social practice with diverse meaning and value beyond health research.